THE POWER OF BONDING SOCIAL CAPITAL BEHIND THE PROGRESS OF A LEADING TELECOMMUNICATIONS COMPANY - Nine, Denita Indah; Sugianto, Helena Anggraeni Tjondro; Ilis, Kristinia (Graduate Program of Universitas Tarumanagara, 2024)
This research departs from a phenomenon of a very advanced company for telecommunications in Indonesia. This progress is shown by the net profit it obtained in 2021 of IDR 3,443 trillion. Entering the composition of their HRD team, there was a group of young people, not a group of senior people who had a lot of experience in the business world. Therefore, through this research, we want to get an overview of what is the secret of the company's success through its HRD Team. The research method uses qualitative methods with an ethnographic approach. Based on the results of the study, it was found that one of the secrets behind this success is due to the existence of social capital bonding among young people who sit on the HRD Team. The noble values instilled by the company become values that are lived together so that trust is created among them. This trust forms a social network and eventually becomes a bonding social capital because it brings profits to the company.